Characterization of vermiculite by XRD and spectroscopic techniques (2009)
A natural mineral from Santa Marta-Colombia used as the starting material in the synthesis of pillared clays has been characterized by several techniques, including X-ray diffraction, X-ray fluorescence, electronic paramagnetic resonance, aluminum nuclear magnetic resonance and scanning electron microscopy. The information revealed that the mineral corresponds to trioctahedral vermiculite. The identification of this mineral is valuable in the control of reduction charge and pillaring processes on these materials to obtain more complex solids like the ones required to specific catalytic applications.